2014
DOI: 10.1084/jem.20132103
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve controls resolution and pro-resolving mediators of inflammation

Abstract: Axonal guidance molecule netrin-1 promotes resolution of inflammation, with netrin-1 and resolvin D1 mutually inducing each other’s expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 32 publications
2
153
1
1
Order By: Relevance
“…Previous work also suggested that the administration of netrin 1 inhibits inflammation in several models of animal disease (36,37), but in our CIA mice, an anti-inflammatory effect of netrin 1 was not detected. Indeed, netrin 1 may not always exhibit anti-inflammatory activity, and contradictory results have been reported.…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 83%
“…Previous work also suggested that the administration of netrin 1 inhibits inflammation in several models of animal disease (36,37), but in our CIA mice, an anti-inflammatory effect of netrin 1 was not detected. Indeed, netrin 1 may not always exhibit anti-inflammatory activity, and contradictory results have been reported.…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 83%
“…36 Furthermore, vagal denervation promotes persistent inflammation through failure to regulate resolution of inflammation. 37 The triad of inflammation, oxidative stress, and impaired baroreflex sensitivity is well recognized in the chronic development of cardiometabolic disease. 38 In conscious rats, loss of baroreflex function impedes attenuation of peripheral ( joint) inflammation, mediated by sympathetic neural drive.…”
Section: Discussionmentioning
confidence: 99%
“…71 Importantly, the regulation of pro-resolving mediators appear to be influenced by neuronal functioning and may be reduced after neuronal injury and dysfunction associated with a reduction in Netrin-1 affecting resolvin D1 production. 72 Figure 3 (a) Normal nociceptor response to a noxious stimulus is shown. (b) Neuroplasticity in the first-order neuron (peripheral sensitization).…”
Section: Peripheral Sensitizationmentioning
confidence: 99%